Novel phytoandrogens and lipidic augmenters from Eucommia ulmoides - Ong Victor YC; Tan Benny KH (BMC, 2007)
Abstract Background Plants containing compounds such as the isoflavonoids, with female hormone-like effects that bind to human estrogen receptors, are known. But none has been previously shown to have corresponding male hormone-like effects that interact with the human androgen receptor. Here, we report that the tree bark (cortex) of the Gutta-Percha tree Eucommia ulmoides possesses bimodal phytoandrogenic and hormone potentiating effects by lipidic components. Methods The extracts of E. ulmoides were tested using in-vitro reporter gene bioassays and in-vivo animal studies. Key compounds responsible for the steroidogenic effects were isolated and identified using solid phase extraction (SPE), high performance liquid chromatography (HPLC), thin layer chromatography (TLC), gas chromatography-mass spectroscopy (GC-MS), electron spray ionisation-mass spectroscopy (ESI-MS) and nuclear magnetic resonance (NMR). Results The following bioactivities of E. ulmoides were found: (1) a phenomenal tripartite synergism exists between the sex steroid receptors (androgen and estrogen receptors), their cognate steroidal ligands and lipidic augmenters isolated from E. ulmoides, (2) phytoandrogenic activity of E. ulmoides was mediated by plant triterpenoids binding cognately to the androgen receptor (AR) ligand binding domain. Conclusion In addition to well-known phytoestrogens, the existence of phytoandrogens is reported in this study. Furthermore, a form of tripartite synergism between sex steroid receptors, sex hormones and plant-derived lipids is described for the first time. This could have contrasting clinical applications for hypogonadal- and hyperlipidaemic-related disorders.